Photochemical Internalization of Etoposide Using Dendrimer Nanospheres Loaded with Etoposide and Protoporphyrin IX on a Glioblastoma Cell Line - Martin Hsiu-Chu Lin; Li-Ching Chang; Chiu-Yen Chung; Wei-Chao Huang; Ming-Hsueh Lee; Kuo-Tai Chen; Ping-Shan Lai; Jen-Tsung Yang (MDPI AG, 2021)
Glioblastoma multiforme (GBM) is the most common malignant primary neoplasm of the adult central nervous system originating from glial cells. The prognosis of those affected by GBM has remained poor despite advances in surgery, chemotherapy, and radiotherapy. Photochemical internalization (PCI) is a release mechanism of endocytosed therapeutics into the cytoplasm, which relies on the membrane disruptive effect of light-activated photosensitizers. In this study, phototherapy by PCI was performed on a human GBM cell-line using the topoisomerase II inhibitor etoposide (Etop) and the photosensitizer protoporphyrin IX (PpIX) loaded in nanospheres (Ns) made from generation-5 polyamidoamine dendrimers (PAMAM(G5)). The resultant formulation, Etop/PpIX-PAMAM(G5) Ns, measured 217.4 ± 2.9 nm in diameter and 40.5 ± 1.3 mV in charge. Confocal microscopy demonstrated PpIX fluorescence within the endo-lysosomal compartment, and an almost twofold increase in cellular uptake compared to free PpIX by flow cytometry. Phototherapy with 3 min and 5 min light illumination resulted in a greater extent of synergism than with co-administered Etop and PpIX; notably, antagonism was observed without light illumination. Mechanistically, significant increases in oxidative stress and apoptosis were observed with Etop/PpIX-PAMAM(G5) Ns upon 5 min of light illumination in comparison to treatment with either of the agents alone. In conclusion, simultaneous delivery and endo-lysosomal co-localization of Etop and PpIX by PAMAM(G5) Ns leads to a synergistic effect by phototherapy; in addition, the finding of antagonism without light illumination can be advantageous in lowering the dark toxicity and improving photo-selectivity.